1990
DOI: 10.1677/joe.0.1260229
|View full text |Cite
|
Sign up to set email alerts
|

Development of a new Leydig cell population after the destruction of existing Leydig cells by ethane dimethane sulphonate in rats: an autoradiographic study

Abstract: The formation of new Leydig cells in adult male rats was studied after the complete destruction of the original population by ethane dimethane sulphonate (EDS). Following administration of EDS, proliferating interstitial cells were labelled in a pulse-chase experiment by way of three [3H]thymidine injections on days 2, 3 and 4 after EDS administration. Some of the newly formed Leydig cells found 14 days after EDS administration were labelled with [3H]thymidine, indicating that these Leydig cells were derived f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 0 publications
3
37
1
Order By: Relevance
“…Some studies reported Leydig cell proliferation in rat testis after selective Leydig cell destruction by ethylene dimethane sulfonate [13,14,15,16]. Leydig cell proliferation was shown with normal endocrinological function after 3 weeks of destruction [14,15,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies reported Leydig cell proliferation in rat testis after selective Leydig cell destruction by ethylene dimethane sulfonate [13,14,15,16]. Leydig cell proliferation was shown with normal endocrinological function after 3 weeks of destruction [14,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Leydig cell proliferation was shown with normal endocrinological function after 3 weeks of destruction [14,15,16]. Increase in LH was proposed to be important for Leydig cell differentiation and proliferation [13,17].…”
Section: Discussionmentioning
confidence: 99%
“…Other data indicate that testicular macrophages also play an important role in regulating LC regeneration in EDS-treated rats (Gaytan et al, 1994a,b). While the initial recruitment and proliferation of LC precursors occurs in the absence of LH and is presumed to be paracrine mediated, it appears that the final differentiation of these precursors into adult LCs is an LH-dependent process (Teerds et al, 1988(Teerds et al, , 1989a(Teerds et al, , 1990a.…”
Section: The Adult Lcmentioning
confidence: 99%
“…But the cells showed strong adherence in primary culture and grew into typical epithelioid-like cells, probably because of the simplified procedure and shortened operation time. In addition, the macrophages and Leydig cells located in the testicular interstitium experience complex paracrine effects that promote cell growth and development and hormone synthesis [14,15], and the formation of new Leydig cells in adult male animals was derived from mesenchymal cells when the original Leydig cell population was destroyed [16,17]. Moreover, adult Leydig cells and mesenchymal cells per testis increased linearly from birth to postpuberty with a ratio of 2:1 respectively, indicating there were considerable mesenchymal cells in adult animals [18].…”
mentioning
confidence: 99%